2022
DOI: 10.3389/fsurg.2022.785676
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Anesthesia and Acute Smell Alterations in Spine Surgery: A “Sniffing Impairment” Influencing Refeeding?

Abstract: Medications for general anesthesia can cause smell alterations after surgery, with inhalation anesthetics being the most acknowledged drugs. However, spine patients have been poorly studied in past investigations and whether these alterations could influence the refeeding remains unclear. This research aims to observe detectable dysosmias after spine surgery, to explore any amplified affection of halogenates (DESflurane and SEVoflurane) against total intravenous anesthesia (TIVA), and to spot potential repercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Although we used an olfactory identification test, this age effect could contribute to the greater postoperative decline in our older cohort. Overall, we show a decrease in median olfactory identification score on the first postoperative day, which corroborates existing studies showing similar results either at 3 hours [ 9 11 ] or, using the discrimination modality, within 15 hours [ 12 ] postoperatively. In two of them, olfactory results were retested again at least 3 days postoperatively and came back to baseline [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although we used an olfactory identification test, this age effect could contribute to the greater postoperative decline in our older cohort. Overall, we show a decrease in median olfactory identification score on the first postoperative day, which corroborates existing studies showing similar results either at 3 hours [ 9 11 ] or, using the discrimination modality, within 15 hours [ 12 ] postoperatively. In two of them, olfactory results were retested again at least 3 days postoperatively and came back to baseline [ 10 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several reports have been published over the years, mainly describing isolated cases of patients with sudden postoperative onset of medium to long-lasting olfactory or gustatory dysfunction [ 4 8 ]. On the other hand, some small-sized studies have shown a possible detrimental effect of the use of sevoflurane compared to other anesthetic agents on immediate postoperative olfactory function [ 9 12 ]. In a recent study, age was correlated to poorer postoperative olfactory performances, thereby suggesting interactions between cognitive impairment, which is more prevalent with age, [ 13 ] and olfactory dysfunction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is room for more comprehensive initiatives. Even in the absence of physical and mental impediments, a patient may eat only half of the calories served in the first days after spine surgery [ 49 ], with the other half possibly posing a risk of silent aspiration from unnoticed dental occlusion disorders, xerostomia, periodontal disease, or ill-fitting dentures [ 50 ]. Since osteoarthritis can also affect the hands, elbows, and shoulders, it is reasonable to think that even if the patient is able to move to the bathroom and brush their teeth, some may have difficulty handling a toothbrush.…”
Section: Unhealthy Oral Health Conditions Might Pose a Risk To Recove...mentioning
confidence: 99%
“…Alcoholic beverages, along with caffeinated and sugar-sweetened drinks, negatively impact the physiology of water balance and, therefore, should be avoided. A large proportion of seniors regularly consume a moderate amount of alcohol, and the aging process is known to increase the risk of dehydration [ 3 , 4 ]. Therefore, old patients, in particular, ought to be advised to make choices on what to drink in view of the upcoming operation, including refraining from dehydrating drinks and, thus, preferring water as early as feasible, given that the restoration of fluids and electrolyte losses might take a few days [ 5 ].…”
Section: Preoperative Preparation For Patients Undergoing Orthopedic ...mentioning
confidence: 99%